Abstract 020: Undulating Flow Velocities as an Induced Test of Autoregulation After Thrombectomy for Acute Ischemic Stroke - Aya Mikkawi; Qasem N Alshaer; Mahmoud Mohammaden; Diogo Haussen; Aaron Anderson (Stroke: Vascular and Interventional Neurology)
Introduction Loss of autoregulation after endovascular therapy (EVT) for large‐artery acute ischemic stroke (AIS) is well documented. [1] This might result in worse outcomes, despite successful recanalization, from hyper‐ or hypoperfusion with a risk for hemorrhagic conversion or larger stroke volume, respectively. Transcranial doppler (TCD) was previously used to document this phenomenon using spontaneous fluctuations in reactivity. Herein, we present a patient with suspected obstructive sleep apnea (OSA) with undulating flow velocities on TCD, serving as a test for induced vasoreactivity with pre‐ and post‐EVT TCD. Methods A case‐report. Results A middle‐aged patient was admitted with acute left cerebellar stroke (figure 1A). An Embolic etiology was suspected and a 20‐minuteTCD was done for spontaneous emboli detection on bilateral middle cerebral arteries (MCA). The patient fell asleep during the study and it incidentally revealed a bilaterally symmetric undulating velocity, which is a pattern that was previously described with OSA as a result of vasomotor response to multiple apnea and hypopnea episodes occurring in succession (Figure 1D – Pre‐EVT). [2] This pattern indicates intact vasomotor reactivity to fluctuating O2 and CO2 levels during episodes of apnea. Six days later, the patient developed acute right MCA stroke (Figure 1B) and was treated with EVT with successful reperfusion (TICI 2B67) (Figure 1C). TCD was repeated after EVT, and the previously seen undulating pattern was lost with significantly reduced variability on the right MCA compared to the contralateral side (figure 1E – Post‐EVT). This indicates a significant reduction in vasomotor reactivity and autoregulatory capacity of the right MCA. Follow up imaging revealed hemorrhagic conversion in the bed of the stroke with intraparenchymal bleeding (PH1) (Figures 1F‐H). This case is unique since it provides an induced test of autoregulation and compares pre‐ and post‐EVT autoregulatory function. Prior reports did not use any stressors to test for autoregulation. While in this case, apnea served as a natural test for autoregulation allowing for easier detection. This can serve as a future marker that can be easily quantified and might guide post‐EVT care. Using breath holding maneuvers or medication (e.g., Acetazolamide) might be considered in the future to quantify the autoregulatory response. Further studies are required to investigate the utility of induced, instead of spontaneous, autoregulation assessment post‐EVT to guide blood pressure goals and the duration of strict blood pressure control after endovascular intervention. Conclusion Induced tests for autoregulation using TCD might be feasible and should be considered in the future as an easy method for quantifying autoregulation post‐EVT. Further studies are required to clarify the utility of this biomarker in guiding post‐EVT care.